2018
DOI: 10.1016/j.jcmg.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in 3-Dimensional Left Ventricular Mechanics With Anthracycline Chemotherapy Are Associated With Systolic and Diastolic Dysfunction

Abstract: Anthracyclines result in early and persistent abnormalities in 3D mechanics. The 3D LVEF and strain measures are associated with concurrent and subsequent systolic dysfunction, and concurrent diastolic dysfunction. Future research is needed to define the mechanisms and clinical relevance of abnormal 3D mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 22 publications
3
39
0
1
Order By: Relevance
“…20 Although less feasible and reproducible, 2D-or 3D-derived global circumferential strain may also serve as additional markers of myocardial dysfunction but require more studies for validation. 21,22 GLS surveillance may become a more sensitive strategy for early detection of cardiotoxicity and guide timing of cardioprotective treatment (Figure 1). Several cardiotoxic cancer treatments including AC and trastuzumab have been shown to cause a persistent reduction in LVEF and GLS.…”
Section: General Principlesmentioning
confidence: 99%
“…20 Although less feasible and reproducible, 2D-or 3D-derived global circumferential strain may also serve as additional markers of myocardial dysfunction but require more studies for validation. 21,22 GLS surveillance may become a more sensitive strategy for early detection of cardiotoxicity and guide timing of cardioprotective treatment (Figure 1). Several cardiotoxic cancer treatments including AC and trastuzumab have been shown to cause a persistent reduction in LVEF and GLS.…”
Section: General Principlesmentioning
confidence: 99%
“…Cardiotoxicity per se from digitalis, mercurial diuretics and local anesthetics was first reported 70 years ago [ 4 , 5 , 6 ], but attributed to cancer therapeutics in the 1970s [ 7 ]. The most commonly recognised phenotype is left ventricular systolic dysfunction (LVSD), but cardiotoxicity may also manifest as systolic or diastolic left ventricular dysfunction (LVD), propensity to arrhythmia, vascular dysfunction, myocarditis, hypertension or pericardial presentations [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…2D strain has proven useful to detect subclinical LV dysfunction in cancer patients [72]. Several studies have attempted to determine the clinical usefulness of 3D strain in cancer patients who had been treated with cardiotoxic anticancer drugs [27,40,54,[73][74][75][76]. All but one study showed a significant reduction of 3D global strain during and after cardiotoxic anticancer drugs, compared with baseline (Table 4).…”
Section: Cardio-oncologymentioning
confidence: 99%